Dynamic Change in Serum Alpha-fetoprotein Level Predicts Treatment Response and Prognosis of Alpha-fetoprotein-producing Gastric Cancer. Issue 47 (20th November 2020) - Wang, Ruhan; Li, Jing; Xu, Dan; Li, Ruiyang; Gong, Ping
Abstract : Abstract: Alpha-fetoprotein (AFP)-producing gastric cancer (AFPGC) is rare and associated with a suboptimal prognosis. The aim of this retrospective study was to identify prognostic factors, with a particular focus on the dynamics of serum AFP levels during treatment, in AFPGC patients. Data of patients with pathologically diagnosed primary gastric cancer treated with various modalities electronically collected in the medical management systems of 2 hospitals (ie, Shihezi People's Hospital and Shihezi Hospital) in Shihezi city, northwest China, from January 2007 to October 2018 were reviewed. Patients with AFPGC were identified based on serum AFP levels. Associations of the change in serum AFP levels and clinicopathological parameters with treatment response, including the overall response rate and disease control rate, and outcomes, including overall survival (OS) and progression-free survival (PFS), were compared among different groups. Of 2354 patients diagnosed with gastric cancer, 96 patients with AFPGC were identified. The objective response rate and disease control rate were significantly higher in patients whose AFP level decreased by ≥50% than in patients whose AFP level decreased by <50% (68.8% vs. 40.6%, and 87.5% vs. 53.1%, respectively, both P < .05). The median OS and PFS were 32.0 (4-74) and 24.0 (1-66) months, respectively, in patients with a ≥50% decline in AFP, and 12.5 (0-69) and 9.0 (0-63) months, respectively, in those with a <50% decline in AFP (both P < .05). On univariate and multivariate analyses, tumor, node, metastasis staging classification stage, liver metastasis, curable surgery, and the decline in the serum AFP level were associated with OS and PFS. A significant decline in the serum AFP level was associated with good treatment response and prognosis in AFPGC. Along with a decline in the serum AFP level, tumor, node, metastasis staging classification stage, liver metastasis, and curable surgery were also independent factors associated with prognosis.